Analysis of Passenger Satisfaction on Work Environment and Employee Performance at Minangkabau International Airport - Desri, Syuryatman; Adinarta, Bima Satria; Fadilla, Sarah Faikhotul (Asian Journal of Management Analytics, 2023)
With the increasing number of passengers boarding airplanes, the government is trying to increase the capacity of Indonesian aircraft. The business world has entered a globalization era, meaning that competition is getting stronger, not only for domestic companies but even for multinational companies. The purpose of this research is to determine the satisfaction of airplane passengers with the work environment and the performance of employees at Minangkabau International Airport. The population in this study were passenger passengers who had traveled through Minangkabau International Airport, with a sample of 100 respondents. Data analysis results from the questionnaire were processed using quadrant analysis with the Importance Performance Analysis (IPA) method and the Customer Satisfaction Index (CSI) method. The results of the data analysis show that, overall, passengers are satisfied with the performance provided by the airport.